2018
DOI: 10.1002/ajmg.a.38689
|View full text |Cite
|
Sign up to set email alerts
|

Current clinical evidence does not support a link between TBL1XR1 and Rett syndrome: Description of one patient with Rett features and a novel mutation in TBL1XR1, and a review of TBL1XR1 phenotypes

Abstract: Funding informationBlue Bird Circle, Houston Mutations in MECP2 are causative for Rett syndrome (RTT, OMIM 312750) in 95-97% of typical cases (Amir et al., 1999; Neul et al., 2008). In order to diagnose typical Rett syndrome, a patient must have undergone developmental regression after developing neurotypically in the first 6-18 months. Additional obligatory features are loss of acquired language, loss of purposeful hand skills, gait abnormalities (dyspraxia), and Rett-typical hand stereotypies such as hand-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The comparison showed that for ‘confirmed’ genes classified by the DECIPHER, only three genes, KMT2E , TBL1XR and TRIP12 , were not covered by the CES. These three genes were all rarely reported in previous studies, which should have little influence on the diagnosis of DD patients with behavioural troubles in this study 34–37. Additionally, we used ‘behavioural abnormalities’ as the search term and extracted a list containing 99 genes from the OMIM database.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison showed that for ‘confirmed’ genes classified by the DECIPHER, only three genes, KMT2E , TBL1XR and TRIP12 , were not covered by the CES. These three genes were all rarely reported in previous studies, which should have little influence on the diagnosis of DD patients with behavioural troubles in this study 34–37. Additionally, we used ‘behavioural abnormalities’ as the search term and extracted a list containing 99 genes from the OMIM database.…”
Section: Discussionmentioning
confidence: 99%
“…Surface plasmon resonance assays show that MeCP2-TBLR1 (the direct binding subunit of the NCoR complex) interaction is relatively weak (K D 9.5 ± 0.5 µM), which could be due to a lack of physiological context in vitro, or it could indicate transient binding (Kruusvee et al, 2017). Evidence for NCoR mutations specifically causing Rett syndrome is lacking (Sakaguchi et al, 2018;Zaghlula et al, 2018). Instead, they can cause intellectual disabilities, rather than RTT, per se, similar to misregulation of other MeCP2-associated processes such as mRNA splicing or miRNA biogenesis, suggesting comparable importance of MeCP2's differing roles (Young et al, 2005;Ha and Kim, 2014).…”
Section: Mecp2 As An Rna Interacting Proteinmentioning
confidence: 99%
“…These two variants lie in the inner side of the ringshaped protein, formed by the eight WD40 domains, suggesting a similar pathogenic mechanism. There are other several patients with reported pathogenic SNVs in TBL1XR1 [1][2][3][4][5][6][7][8] showing different neurological phenotypes (ID, autism, epilepsy, schizophrenia, Rett features) but in only a few of them dysmorphic features are reported, some of these findings are present in Pierpont syndrome, 4,5 but not others 3,8 (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic mutations in TBL1XR1 gene were first described in 2012 1,2 in two patients with autism spectrum disorders (ASD). After that, single nucleotide pathogenic variants (SNVs) have been reported in several cases: a girl without dysmorphic features that developed West syndrome at 5 months of age and later was diagnosed with autism with Rett-like features 3 ; 6 patients, all with global developmental delay and no dysmorphic features, three of them with autism, diagnosed in the Deciphering Developmental Disorders (DDD) study 4 ; a young man with intellectual disability (ID), autism and dysmorphic features 5 ; a patient with sporadic schizophrenia 6 ; a 7-year-old girl with Rett features and no dysmorphic findings 7 ; and a 7-year-old boy with autism and facial dysmorphism. 8 In 2016, Heinen et al 9 reported the same SNV pathogenic variant, p.(Tyr446Cys), in TBL1XR1 gene in six patients clinically diagnosed with Pierpont syndrome.…”
Section: Introductionmentioning
confidence: 99%